DISCURSO DE ÓDIO HOMOFÓBICO NO FACEBOOK: UMA ANÁLISE DOS COMENTÁRIOS DAS PUBLICAÇÕES DE NOTÍCIAS NOS CIBERJORNAIS DE CAMPO GRANDE - MS. - Lucas Souza da Silva (2021)
This work aims to analyze the hate speech against the LGBTQIA+ population in the comments of news publications on Facebook and the impact of this practice on the maintenance of prejudice and discrimination of the LGBTQIA+ population. The work intends to address the context of cyberspace, digital interactivity and the growing appropriation of journalistic companies of social networks for the transmission of news and the consequences of this phenomenon in the manifestation of hate speech on Facebook. Through the theoretical framework of Critical Discourse Analysis (FAIRCLOUGH, 1992) and Content Analysis (BARDIN, 2011) we sought to systematize and identify ideological traits in the propagation and circulation of comments classified as hate speech against the LGBTQIA+ population in publications of news on Facebook from the three main communication vehicles in Mato Grosso do Sul: Correio do Estado, Campo Grande News and Midiamax.